VIDEO STREAMING DENGAN VIDEOLAN PROJECT - Aprinal Adila.A; Yustini yustini (Teknik Elektro Politeknik Negeri Padang, 2009)
Streaming is process of continuing data sending by broadcasting trough internet which showed by streaming application at PC client. The sending data packaging is compressing to make sending process is easy. Streaming can be done by input media variation and client has a change to benefit just after server sending the distreaming data and running in VLC media player. VideoLAN Client (VLC) is a media to streaming which can be applied as transmitter and receiver. VLC can compress and decompress audio and video data from some input media. It shows data result of streaming which have picture and voice quality as well as the source.